Efficacité de rétention des polluants par les marais Ciranga et Kabamba du Lac Kivu, République Démocratique du Congo - Dieudonné N. Zirirane; J.G.M. Majaliwa; B.J.B. Muhigwa; N.G. Mushagalusa; K. Karume; M. Bagalwa (VertigO)
Wetlands are more and more threatened by anthropogenic activities reducing their pollutant filtering capacity of waters. This study determined the pollutant retention efficiency of Ciranga and Kabamba wetlands in Lake Kivu basins. Water samples were collected once a month for a period of one year (August, 2011 in July, 2012) from the inlet and the outlet of the wetland, and at seven other locations in the wetland with different types of vegetation. The pollutant retention efficiency was computed as a relative change in a given pollutant concentration to the respective inlet concentration. Result showed that Ciranga and Kabamba wetlands retention efficiency varied over-time and for the type of vegetation and land use. The Ciranga wetland had a relatively higher retention efficiency than Kabamba wetland. The nutrient retention efficiency of Ciranga is 13% for Nitrogen. For Kabamba wetlands, the retention efficiency is about 2% for phosphorus. The concentration of phosphorus (0,5 µmole/l) is high in the river Lwiro crossing in Ciranga wetland. But the retention of Nitrogen is high in the Kabamba wetland. The Kabamba wetland was drained and transformed into farming land, its natural function of purification was reduced. Judicious wetland restoration measures are needed in order to stabilize Lake Kivu and other important ecosystems of the region